A two-layer control strategy of the wind farm participating in grid frequency regulation - Hui Fan; Ming Tang (Alexandria Engineering Journal, 2022)
This paper proposes a two-layer control strategy of wind farm participating in grid frequency regulation for problems caused by the direct switching of FR power distribution and wind turbine control strategy. At the wind farm layer, FR scenarios are divided. And a turbine grouping strategy is proposed according to the running status at the current and next moments, and the current system FR demand, i.e., increase or decrease power. According to the FR capability of wind turbines, the turbines are arranged to participate in FR in sequence. Consequently, the power support for the corresponding frequency fluctuation of the wind turbine is achieved, and the insufficient FR capacity caused by equal distribution is avoided. At the turbine layer, a proportional coefficient model is created based on the optimized combination FR mode of participating in FR. As a result, smooth switching of different FR modes is realized without modifying the original turbine structure. It makes upgrades simple and easy. A simulation model including four turbines and two domains is created in Matlab/Simulink, verifying the validity of the proposed strategy.